Structural dynamics of heme-copper oxidases and nitric oxide reductases: Time-resolved step-scan Fourier transform infrared and time-resolved resonance Raman studies - Pinakoulaki, Eftychia; Koutsoupakis, Constantinos; Stavrakis, Stavros; Aggelaki, Marialena; Papadopoulos, George; Daskalakis, Vangelis; Varotsis, Constantinos (My University, 2005)
Of the spectroscopic methods available for the characterization of the dynamics of heme protein active sites, time-resolved resonance Raman spectroscopy (TR 3) is a powerful technique because excitation within the heme π-π* electronic absorption transitions selectively enhances vibrational modes of the heme and bound-proximal/distal ligands without the interference from the modes associated with the protein matrix. On the other hand, time-resolved step-scan (TRS 2) Fourier transform infrared (FTIR) spectroscopy has the sensitivity and resolution to detect, in addition to ligands bound to metal centers and the kinetics of ligand photodissociation, transient changes at the level of individual amino acids during protein action. This review outlines the application of both TR 3 and TRS 2-FTIR to heme-copper oxidases and nitric oxide reductases
Keywords: Raman spectroscopy; Copper; Nitric oxide; Fourier transform infrared spectroscopy; Structural dynamics; Heme; Ligands